2014
DOI: 10.1089/scd.2013.0611
|View full text |Cite
|
Sign up to set email alerts
|

Mutation Frequency Dynamics inHPRTLocus in Culture-Adapted Human Embryonic Stem Cells and Induced Pluripotent Stem Cells Correspond to Their Differentiated Counterparts

Abstract: The genomic destabilization associated with the adaptation of human embryonic stem cells (hESCs) to culture conditions or the reprogramming of induced pluripotent stem cells (iPSCs) increases the risk of tumorigenesis upon the clinical use of these cells and decreases their value as a model for cell biology studies. Base excision repair (BER), a major genomic integrity maintenance mechanism, has been shown to fail during hESC adaptation. Here, we show that the increase in the mutation frequency (MF) caused by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
25
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 73 publications
0
25
0
Order By: Relevance
“…The hiPSC line cl1 was obtained from Dr. Majlinda Lako, Institute of Genetic Medicine, Newcastle University and the iPSC lines MDMD2Se were derived in our laboratory from human skin biopsies (Krutá et al 2014). The hESCs and iPSC lines were propagated on mitotically inactivated mouse embryonic fibroblasts (Dvorak et al, 2005).…”
Section: Preparation Of Hipsc and Hesc Cardiomyocyte Clustersmentioning
confidence: 99%
“…The hiPSC line cl1 was obtained from Dr. Majlinda Lako, Institute of Genetic Medicine, Newcastle University and the iPSC lines MDMD2Se were derived in our laboratory from human skin biopsies (Krutá et al 2014). The hESCs and iPSC lines were propagated on mitotically inactivated mouse embryonic fibroblasts (Dvorak et al, 2005).…”
Section: Preparation Of Hipsc and Hesc Cardiomyocyte Clustersmentioning
confidence: 99%
“…the colony is the true unit of the hESC population 21 . Therefore, dissociation of a colony to a single cell suspension, which is commonly used in the literature to assess hESC growth rate 30,31 may result in a different estimation of DT, at least due to the lag period needed for re-establishing the colony. Certainly more studies are required to test this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…hESCs were shown to accumulate various types of mutations (2)(3)(4). At the same time and based mostly on the reporter gene assays, hESCs were reported to have lower mutant frequency (MF) than their differentiated counterparts (5)(6)(7). In order to maintain their genomic integrity, hESCs were shown to have increased mRNAs and protein levels of several DNA repair genes (8)(9)(10).…”
mentioning
confidence: 99%
“…In mammalian cells, BER attempts to repair clustered damaged bases that are on the opposing strands within a few helical turns by generating double-strand breaks (DSBs) (19,20), which are characterized by short homologous overhangs. We previously demonstrated that hESCs (with elevated BER) release large amounts of ABBREVIATIONS: gH2AX, H2A histone family member X phosphorylated on Ser139; 53BP1, p53 binding protein 1; BER, base excision repair; CCTL, Centre for Cell Therapy line; Cdc25C, cell division cycle 25C; Chk, checkpoint kinase; cNHEJ, canonical nonhomologous EJ; DNA PKcs, DNA-dependent protein kinase catalytic subunit; DSB, DNA doublestrand break; EJ, end-joining; GFP, green fluorescent protein; hESC, human embryonic stem cell; HPRT, hypoxanthine phosphoribosyltransferase; HR, homologous recombination; ICC, immunocytochemistry; IR, irradiation; Lig, ligaseMF, mutant frequency; MMEJ, microhomologymediated EJ; Nu7026, 2-(morpholin-4-yl)-benzo[h]chromen-4-one; PARP1, poly (ADP-ribose) polymerase 1; pChk1, phosphorylated Chk1; pChk2, phosphorylated Chk2; PFGE, pulse-field gel electrophoresis; PolQ, DNA polymerase u; Rad51, Rad51 recombinase (recombination protein A homolog); SCE, sister chromatid exchange; siRNA, small interfering RNA; WB, Western blot DSBs upon induction with IR (5,14). Such DSBs trigger phosphorylation of histone H2A family member X at Ser139 and form gH2AX foci, which serve as a biomarker of DSBs (21) and can lead to retardation of cell cycle progression.…”
mentioning
confidence: 99%
See 1 more Smart Citation